2016
DOI: 10.1007/s10995-016-2013-1
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents and Long-Acting Reversible Contraception: Lessons from Mexico

Abstract: Objectives We describe current use of long acting reversible contraception LARC (tier 1), hormonal (tier 2), barrier and traditional contraceptive methods (tier 3) by adolescent women in Mexico. We test whether knowledge of contraceptive methods is associated with current use of LARC. Methods We used the 1992, 1997, 2006, 2009 and 2014 waves of a nationally representative survey (ENADID). We used information from n = 10,376 (N = 3,635,558) adolescents (15–19 years) who reported ever using any contraceptive met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 19 publications
3
19
0
6
Order By: Relevance
“…Studies examining LARC use in non-sex-worker populations have rarely found a clear association with age, 23,24 and have reported mixed results regarding education. 23,26 Knowledge and positive attitude to family planning were correlates of LARC use, consistent with findings in other populations. 26 Social norms and contraceptive self-efficacy may lie on the same causal pathway as positive attitude, or may measure the same underlying construct.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Studies examining LARC use in non-sex-worker populations have rarely found a clear association with age, 23,24 and have reported mixed results regarding education. 23,26 Knowledge and positive attitude to family planning were correlates of LARC use, consistent with findings in other populations. 26 Social norms and contraceptive self-efficacy may lie on the same causal pathway as positive attitude, or may measure the same underlying construct.…”
Section: Discussionsupporting
confidence: 87%
“…23,26 Knowledge and positive attitude to family planning were correlates of LARC use, consistent with findings in other populations. 26 Social norms and contraceptive self-efficacy may lie on the same causal pathway as positive attitude, or may measure the same underlying construct. Education about LARCs has been found to improve attitude and uptake.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Recent estimates indicate that in Mexico 38 out of 1000 women of reproductive age have had clandestine abortions as a result of not having the necessary contraceptive methods [19]. Inconsistent use of contraceptives is also a problem experienced by young women [20]. The second most significant variable was marital status, where women never in union had a much greater unmet need for contraception than women currently in union.…”
Section: Discussionmentioning
confidence: 99%
“…Se perciben supuestas barreras legales, relacionadas con el consentimiento informado, la autorización de los padres, etc., pero también existen mitos y barreras técnicas, sobre todo en relación con su uso en adolescentes nulíparas (desconocimiento de los criterios internacionales y nacionales de elegibilidad). Evidencias en este sentido pueden observarse en el acceso diferencial a los LARC que tienen las adolescentes, antes o después de un primer embarazo a término, en las diferentes instituciones del sector salud nacional 40 . Es posible, por lo tanto, que la distribución actual de los anticonceptivos utilizados por la población adolescente en México refleje no tanto las barreras, los mitos y los desconocimientos sobre ellos mismos, sino también las barreras y los sesgos radicados en los proveedores de los servicios de salud.…”
Section: Uso De Anticonceptivos En Población Adolescenteunclassified